New Therapeutic Targets and Drugs for the Treatment of Chronic Hepatitis B - Fletcher, Simon P.; Delaney, William E., IV (Seminars in Liver Disease, 2013)
Chronic hepatitis B virus (CHB) is managed effectively with either nucleoside/nucleotide-based or interferon-based therapies. However, most patients receiving these therapies do not establish long-term, durable control of infection after treatment withdrawal. In particular, rates of hepatitis B surface-antigen loss and seroconversion to antisurface-antigen antibody are very low. Thus, novel therapies and treatment modalities are necessary to achieve either elimination of the virus from the liver or durable immune control of hepatitis B virus (HBV) infection in the absence of chronic therapy (“functional cure”). Here the authors review new targets and approaches for treating CHB. These approaches can be divided into two broad categories—those targeting the virus or host factors required by the virus and those targeting the innate or adaptive immune systems. Unfortunately, although a variety of promising strategies have been identified and several new approaches have achieved preclinical validation, relatively few novel drug candidates are in active clinical studies to treat CHB. Thus, functional cure of CHB infection remains an important therapeutic challenge.
Keywords: hepatitis B virus (HBV); antiviral therapy; immunotherapy; chronic hepatitis B; treatment